2012
DOI: 10.5478/msl.2012.3.1.010
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Oxidation of Cysteine Residues in Peroxiredoxin 6 Detected by Twodimensional Gel Electrophoresis and Capillary Liquid Chromatography-Electrospray Mass Spectrometry

Abstract: Artificially oxidized cysteine residues in peroxiredoxin 6 (Prx6) were detected by electrospray interface capillary liquid chromatography-linear ion trap mass spectrometry after the preparation of two-dimensional gel electrophoresis (2D-GE). We used Prx6 as a model protein because it possesses only two cysteine residues at the 47th and 91st positions. The spot of Prx6 on 2D-GE undergoes a basic (isoelectric point, pI 6.6) to acidic (pI 6.2) shift by exposure to peroxide due to selective overoxidation of the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…Existing bottom-up proteomics strategies involve digestion of proteins either in solution or following one- or two-dimensional gel electrophoresis [ 17 ]. Oxidation is commonly encountered in cysteine, methionine, and tryptophan residues during gel electrophoresis and associated sample handling [ 18 20 ]. Whilst oxidation may result in reduced signal-to-noise due to the spread of signal over a number of mass channels, it does not prevent protein identification.…”
Section: Discussionmentioning
confidence: 99%
“…Existing bottom-up proteomics strategies involve digestion of proteins either in solution or following one- or two-dimensional gel electrophoresis [ 17 ]. Oxidation is commonly encountered in cysteine, methionine, and tryptophan residues during gel electrophoresis and associated sample handling [ 18 20 ]. Whilst oxidation may result in reduced signal-to-noise due to the spread of signal over a number of mass channels, it does not prevent protein identification.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular weights of synthetic DR12 (1338.48 Da) and synthetic AR12 (1485.66 Da) were consistent with the theoretical masses of 1338.49 Da and 1485.66 Da, respectively. Some studies have reported that DR12 is a part of peroxiredoxin 6 (Prx6) structure (42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53), which is an enzyme ubiquitously existing in life [31,32]. And several studies reported that AR12 is a part of heat shock proteins derived from human or dairy cows, respectively [33,34].…”
Section: Identification Of Antioxidant Peptidesmentioning
confidence: 99%
“…Abnormal levels of Cys, GSH, and Hcy are related to a number of diseases, which have effects on the normally physiological and pathological functions, such as AIDS, Alzheimer, angiocardiopathy, cancer, liver damage, and osteoporosis. , The analysis and detection of biothiols is significant for the prevention, research, and treatment of the abovementioned diseases and their biological functions. Compared with high-performance liquid chromatography, enzymatic methods, mass spectrometry, electrochemical assays, and Raman scattering, , fluorescence analysis methods , based on fluorescent probes have the advantages of simplicity, high selectivity, and short response time. More importantly, fluorescent probes are widely used in biomedicine, analytical chemistry, and chemical biology because they can carry out real-time monitoring and bio-imaging in organisms.…”
Section: Introductionmentioning
confidence: 99%